2017
DOI: 10.1038/s41398-017-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated peripheral expression of neuregulin-1 (NRG1) mRNA isoforms in clozapine-treated schizophrenia patients

Abstract: Differential expression of neuregulin-1 (NRG1) mRNA isoforms and proteins has been reported in schizophrenia, primarily in post-mortem brain tissue. In this study, we examined 12 NRG1 SNPs, eight NRG1 mRNA isoforms (type I, type I(Ig2), type II, type III, type IV, EGFα, EGFβ, pan-NRG1) in whole blood, and NRG1-β1 protein in serum of clozapine-treated schizophrenia patients (N = 71) and healthy controls (N = 57). In addition, using cultured peripheral blood mononuclear cells (PBMC) from 15 healthy individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Previous findings by us and others support the notion of increased transcription of genes within the NRG–ErbB signaling pathway in schizophrenia. We recently showed in the same cohort used in the current study, an increased expression of three NRG1 transcripts [i.e., NRG1 -EGFα, NRG1 -EGFβ, and NRG1 -typeI (Ig2) ] in TRS compared to controls ( 24 ). In addition, several studies by others have reported increased expression of specific isoforms of NRG1 ( 18 ) and mRNA of down-stream signaling molecules, including PIK3CD, PIK3CB ( 16 , 22 ), and AKT1 ( 22 , 23 ) in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous findings by us and others support the notion of increased transcription of genes within the NRG–ErbB signaling pathway in schizophrenia. We recently showed in the same cohort used in the current study, an increased expression of three NRG1 transcripts [i.e., NRG1 -EGFα, NRG1 -EGFβ, and NRG1 -typeI (Ig2) ] in TRS compared to controls ( 24 ). In addition, several studies by others have reported increased expression of specific isoforms of NRG1 ( 18 ) and mRNA of down-stream signaling molecules, including PIK3CD, PIK3CB ( 16 , 22 ), and AKT1 ( 22 , 23 ) in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 51%
“…Likewise, evidence of dysregulated gene expression of NRG1 ( 18 20 ), ErbB1 / ErbB4 ( 21 ), and PI3K /AKT ( 22 , 23 ) in peripheral tissues [i.e., whole blood, peripheral blood mononuclear cells (PBMCs), monocytes] in schizophrenia has also been shown in people with chronic schizophrenia. Treatment-resistant schizophrenia (TRS) patients represent a considerable subgroup who have significant increases in multiple NRG1 splice variants in peripheral blood ( 24 ). Thus, we may expect the biological interactors (receptors) and mediators (kinase) of this pathway to also be changed.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple risk haplotypes and genetic polymorphisms in both the 5′ and 3′ regions of the NRG1 gene have been linked to schizophrenia 41 Variants linked to schizophrenia have been shown to alter transcription factor binding and to increase transcription of specific NRG1 isoforms, and have been associated with abnormal cortical function and psychotic symptoms 14 , 42 . Moreover, elevated levels of multiple NRG1 mRNA isoforms have been detected in the blood of clozapine-treated schizophrenia patients, with more highly elevated levels frequently detected in those with an earlier age of illness onset 43 .…”
Section: Discussionmentioning
confidence: 99%
“…NRG-1 plays an important role in brain plasticity and development. Moreover, NRG-1 has been found in multiple regions of the adult brain and is involved in the regulation of neurotransmission [79]. ND occurs in individuals with neurodevelopment problems and limited plasticity.…”
Section: Neuregulin-1 In Diseasementioning
confidence: 99%
“…NRG-1 has been one of the most extensively studied genes in SZ [80]. One study conducted in 2017 examined the levels of NRG-1 and EGF in treatment-resistant schizophrenic patients and found decreased or abnormally expressed levels of these proteins [79]. While past research has examined the levels of NRG-1 in the brain [83], future research could look toward understanding the mechanisms regulating NRG-1 expression and function and possible use of NRG-1 as a treatment for ND disorders.…”
Section: Neuregulin-1 In Diseasementioning
confidence: 99%